Mengembangkan Minat dan Bakat Siswa dalam Kegiatan Ekstrakurikuler Bola Voli - Nasori Nasori; Adiman Adiman; Dewi Wahyuni (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine how extracurricular volleyball activities can develop students' interests and talents at SMP Negeri 8 Kota Cirebon. Volleyball is one of the sports that is quite popular among students, but it still faces obstacles such as limited facilities, competition among players, and a lack of focused coaching. Therefore, this study is important to explore the role of extracurricular activities in supporting students' potential. Materials and method. This research employs a qualitative approach using a descriptive method. Data was collected through direct observation, in-depth interviews with students, coaches, and mentors, as well as documentation of volleyball extracurricular activities. The research subjects were seventh-grade students actively participating in volleyball extracurricular activities. Data were analysed inductively through the stages of reduction, presentation, and conclusion drawing. Results. The results of the study indicate that volleyball extracurricular activities have a positive impact on increasing students' interest and developing their talents. Students become more enthusiastic, confident, and demonstrate improved technical skills in the game. Students' interest develops because the activities are designed to be enjoyable and supported by competent coaches. Additionally, these activities also strengthen social aspects such as cooperation, sportsmanship, and discipline. Conclutions. Factors supporting the success of interest and talent development include students' personal motivation, school environment support, and availability of training facilities.